2020
DOI: 10.1167/tvst.9.5.25
|View full text |Cite
|
Sign up to set email alerts
|

Climatic and Environmental Correlates of Dry Eye Disease Severity: A Report From the Dry Eye Assessment and Management (DREAM) Study

Abstract: Correlate climate, weather parameters, and environmental exposures with the severity of symptoms and signs of dry eye disease (DED) in Dry Eye Assessment and Management (DREAM) study participants. Methods: Participants from five distinct climates completed the Ocular Surface Disease Index (OSDI) and were examined for corneal and conjunctival staining, tear breakup time (TBUT), and Schirmer's testing at baseline, 3, 6, and 12 months. Climate, weather parameters, and pollutants including ozone (O 3), carbon mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 22 publications
4
30
0
Order By: Relevance
“…Climatic and environmental changes have differential adverse impacts on dry eye and likely occur in tropical countries where sunlight and wind exposure is immense [2,[18][19][20]. Previous evidence showed that low humidity (< 40%) increased tear evaporation and subsequently worsened dry eye symptoms [21].…”
Section: Plos Onementioning
confidence: 99%
“…Climatic and environmental changes have differential adverse impacts on dry eye and likely occur in tropical countries where sunlight and wind exposure is immense [2,[18][19][20]. Previous evidence showed that low humidity (< 40%) increased tear evaporation and subsequently worsened dry eye symptoms [21].…”
Section: Plos Onementioning
confidence: 99%
“…However, since mean values of both groups were in the normal range, the clinical significance of this finding is uncertain. In another study of 535 U.S. dry eye patients identified by the presence of ocular dryness for greater than 6 months with moderate to severe OSDI scores (25–80), multivariate analyses and partial correlation coefficients revealed TBUT measurements were positively correlated with temperature, humidity, and dew point (ρ = 0.08, 0.18, 0.17, respectively, p < 0.0038) [ 70 ].…”
Section: Effect Of Weather On the Ocular Surfacementioning
confidence: 99%
“…Kuo et al mentioned in their recently published research that bilateral eyes of DED patients may have similar but different ocular surface performance and tear composition [28]. Similar to the research of other authors in our study results, we included the first examined eye because automatic measurement may produce distorted measurements and results from the second examined eye [28,30].…”
Section: Discussionmentioning
confidence: 73%